Answer:
y=3×-11
Step-by-step explanation:
y=m+c
m=7-1÷6-4
m=6÷2
m=3
y=3+c
7=3(6)+c
7-18=c
-11=c
y=3×-11
Answer:
B. 2(-3w+(-11)
Step-by-step explanation:
-3(2w+6)-4=
-6w-18-4=
-6w-22=
2(-3w+(-11)
Answer:
N = -7
Step-by-step explanation:
4 = 1 - n -4
Subtract the numbers first
1 - 4 = -3
Then rearrange the terms
4 = -3 - n
-----> 4 = n - -3
The you add 3 to both sides of the equations
4 + 3 = -n - 3 + 3
The volume of the sphere of radius r is:
V1 = (4/3) * (pi) * (r ^ 3)
Where,
r: sphere radius:
The volume of the sphere of radius 0.3r is:
V2 = (4/3) * (pi) * ((0.3r) ^ 3)
Rewriting:
V2 = (4/3) * (pi) * (0.027 (r) ^ 3)
V2 = 0.027 (4/3) * (pi) * (r ^ 3)
V2 = 0.027V1
The difference is:
V1-V2 = V1-0.027V1 = V1 (1-0.027)
V1-V2 = 0.973 * (4/3) * (pi) * (r ^ 3)
Answer:
the difference in volume between a sphere with radius and a sphere with radius 0.3r is:
V1-V2 = 0.973 * (4/3) * (pi) * (r ^ 3)